2016
DOI: 10.1103/physrevlett.116.131101
|View full text |Cite
|
Sign up to set email alerts
|

New Test of the Gravitational Inverse-Square Law at the Submillimeter Range with Dual Modulation and Compensation

Abstract: By using a torsion pendulum and a rotating eightfold symmetric attractor with dual modulation of both the interested signal and the gravitational calibration signal, a new test of the gravitational inverse-square law at separations down to 295  μm is presented. A dual-compensation design by adding masses on both the pendulum and the attractor was adopted to realize a null experiment. The experimental result shows that, at a 95% confidence level, the gravitational inverse-square law holds (|α|≤1) down to a leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 32 publications
3
88
0
Order By: Relevance
“…For the case of the double brane, the correction also occurs at the scale of r ∼ 1/k, but it has a complex form because of the rich structure of the mass spectrum of the resonance KK modes. According the recent test of the gravitational inverse-square law, the usual Newtonian potential still holds down to a length scale at 59µm [68]. Therefore, the thickness of the brane, 1/k, should be much less than 59µm.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For the case of the double brane, the correction also occurs at the scale of r ∼ 1/k, but it has a complex form because of the rich structure of the mass spectrum of the resonance KK modes. According the recent test of the gravitational inverse-square law, the usual Newtonian potential still holds down to a length scale at 59µm [68]. Therefore, the thickness of the brane, 1/k, should be much less than 59µm.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Substituting Eqs. (5)- (7) into Eqs. (2)-(3), respectively, equating terms with the same time dependence, and working to the lowest order in Ω pr but to all orders in Ω pu , we can obtain…”
Section: The Heisenberg Equationsmentioning
confidence: 99%
“…In addition to this possibility, they found that their model could describe the hierarchy between the Planck mass and the electroweak symmetry breaking scale in terms of the large size of the extra dimensions. Therefore testing general relativity and its Newtonian limit at short distances has become particularly important in light of recent theoretical developments [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on searching for LLI violation in pure-gravity sector for d = 6, which has been widely tested by short-range gravitational experiments, since the short-range experiments are better than other experiments to probe higher dimension coefficients with r-dependence. The best current limit for d = 6 is at 10 −9 m 2 [25], which is given by a combined analysis for lab-based on-ground experiments HUST-2011 [26], HUST-2015 [27], IU-2002 and IU-2012 [28]. Based on the experiment performed in our lab, the test of the gravitational inverse square law, we have proposed a simple scheme to greatly enlarge the LLI violation signal [29].…”
Section: Introductionmentioning
confidence: 99%